2019
DOI: 10.1073/pnas.1806820116
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine neuron-derived IGF-1 controls dopamine neuron firing, skill learning, and exploration

Abstract: Midbrain dopamine neurons, which can be regulated by neuropeptides and hormones, play a fundamental role in controlling cognitive processes, reward mechanisms, and motor functions. The hormonal actions of insulin-like growth factor 1 (IGF-1) produced by the liver have been well described, but the role of neuronally derived IGF-1 remains largely unexplored. We discovered that dopamine neurons secrete IGF-1 from the cell bodies following depolarization, and that IGF-1 controls release of dopamine in the ventral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 74 publications
(105 reference statements)
1
41
0
Order By: Relevance
“…In the mammalian central nervous system, DA controls many processes [262,264], such as feeding and locomotion [265]; it is also involved in the mechanisms of cognition and ‘adaptive’ memory formation, influencing the hippocampal long term potentiation (LTP) [266], and upregulates BDNF in the prefrontal cortex [267]. DA most probably interacts with other neurotransmitters and neuromodulators and, for example, it has been recently demonstrated that midbrain mice DA neurons also release IGF-1 that modulates DA release and concentration as well as neuronal firing [268].…”
Section: Exercise-dependent Production Of Dopamine Endocannabinoimentioning
confidence: 99%
“…In the mammalian central nervous system, DA controls many processes [262,264], such as feeding and locomotion [265]; it is also involved in the mechanisms of cognition and ‘adaptive’ memory formation, influencing the hippocampal long term potentiation (LTP) [266], and upregulates BDNF in the prefrontal cortex [267]. DA most probably interacts with other neurotransmitters and neuromodulators and, for example, it has been recently demonstrated that midbrain mice DA neurons also release IGF-1 that modulates DA release and concentration as well as neuronal firing [268].…”
Section: Exercise-dependent Production Of Dopamine Endocannabinoimentioning
confidence: 99%
“…IGF1R is known as a transmembrane receptor tyrosine kinase which is implicated in the regulation of IGF bioactivity [13]. Interactions between cells utilizing the IGF-1/IGF1R signalling cascades play a key role in the survival of neuronal cells against stress and injury [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…DA neurons present IGF‐1 receptors (IGF‐1R), 173,174 and administration of IGF‐1 prevents degeneration of DA neurons in Parkinson's disease (PD) models through the activation of the PI3K/AKT pathway 175,176 . It has recently been discovered that a large population of VTA and SNc DA neurons present endogenous somatic but not axonal release of IGF‐1 in response to depolarization as a feed‐forward mechanism, blocking somatodendritic release of DA and D2 autoreceptor‐mediated inhibition 174 . Particularly, IGF‐1 activates the mTOR pathway, so specific deletion of IGF‐1 in DA neurons decreases phosphorylation of mTOR downstream element S6 174 .…”
Section: Trophic Factors Regulate Da Homeostasis Through Mtor Pathwaymentioning
confidence: 99%
“…It has recently been discovered that a large population of VTA and SNc DA neurons present endogenous somatic but not axonal release of IGF‐1 in response to depolarization as a feed‐forward mechanism, blocking somatodendritic release of DA and D2 autoreceptor‐mediated inhibition 174 . Particularly, IGF‐1 activates the mTOR pathway, so specific deletion of IGF‐1 in DA neurons decreases phosphorylation of mTOR downstream element S6 174 . IGF‐1 lacking DA neurons also present decreased TH activating phosphorylation in Ser40, whose activity is controlled by mTOR as previously described in DA neurons 154,174 .…”
Section: Trophic Factors Regulate Da Homeostasis Through Mtor Pathwaymentioning
confidence: 99%